Acute Illness and Death in Children With Adrenal Insufficiency - Worth, Chris; Vyas, Avni; Banerjee, Indraneel; Lin, Wei; Jones, Julie; Stokes, Helen; Komlosy, Nicci; Ball, Steven; Clayton, Peter (Frontiers in Endocrinology, 2021)
Background Adrenal Insufficiency (AI) can lead to life-threatening Adrenal Crisis (AC) and Adrenal Death (AD). Parents are trained to prevent, recognise and react to AC but there is little available information on what parents are actually doing at home to manage symptomatic AI. Methods Three approaches were taken: (A) A retrospective analysis of patient characteristics in children and young people with AD over a 13-year period, (B) An interview-aided questionnaire to assess the circumstances around AC in children currently in our adrenal clinic, and (C) a separate study of parent perceptions of the administration of parenteral hydrocortisone. Results Thirteen patients died (median age 10 years) over a thirteen-year period resulting in an estimated incidence of one AD per 300 patient years. Those with unspecified adrenal insufficiency were overrepresented (P = 0.004). Of the 127 patients contacted, thirty-eight (30%) were identified with hospital attendance with AC. Responses from twenty patients (median age 7.5 years) with AC reported nausea/vomiting (75%) and drowsiness (70%) as common symptoms preceding AC. All patients received an increase in oral hydrocortisone prior to admission but only two received intramuscular hydrocortisone. Questionnaires revealed that 79% of parents reported confidence in the administration of intramuscular hydrocortisone and only 20% identified a missed opportunity for injection. Conclusions In children experiencing AC, parents followed ‘sick day’ guidance for oral hydrocortisone, but rarely administered intramuscular hydrocortisone. This finding is discrepant from the 79% of parents who reported confidence in this task. Local training programmes for management of AC are comprehensive, but insufficient to prevent the most serious crises. New strategies to encourage use of parenteral hydrocortisone need to be devised.